PENGARUH HARGA, RELIGIUSITAS, DAN RESILIENSI TERHADAP MINAT BELI PEDAGANG SAYUR KELILING KEC. WONOMERTO KAB. PROBOLINGGO - Afthoni Zein, M. Fathan; Luayyin, Reza Hilmy; Ardli, Muhammad Nabat (JSE: Jurnal Sharia Economica, 2023)
In the world of marketing, products that meet consumer needs and wants will survive in the market. Therefore, consumers tend to consider price and purchase products from well-known brands because of the lower risk. To address this, it is important to understand the influence of variables such as price, religiosity, resilience, halal logo certification, and ethics. This research is a descriptive qualitative study using a questionnaire with a Likert scale of 1-4. The study population consists of mobile vegetable vendors' customers, with a sample of 50 respondents in Wonomerto District. The data were analyzed using SmartPLS technique. The variables analyzed include price, religiosity, resilience, and ethics. The results show that price has a positive and significant influence on the purchase intention towards mobile vegetable vendors, and religiosity has a positive and significant influence on the purchase intention towards mobile vegetable vendors. However, resilience does not have a positive and significant influence on the purchase intention towards mobile vegetable vendors. Keywords: Mobile Vegetable Vendors , Religiosity, Resilience, Price,.